Pengembangan Handout Digital Berbasis Flipbook pada Materi Ekonomi Bisnis dan Administrasi Umum di SMKN 6 Surabaya - Aulia Prinita, Dini; Rosita Dewi Iriyanti; Najwa Dafa Agustina; Luqman Hakim; Amirul Arif (LPPM Politeknik Piksi Ganesha, 2024)
One of the benefits of technology in education is to facilitate student and teacher access to various learning resources. In this digital age, the use of traditional learning media has become less effective. This research aims to create digital handouts in Flipbook form for Business Economics and General Administration material, as well as assessing how feasible these digital handouts are. This research is recommended as research using the development (R&D) method using the ADDIE research design. The feasibility evaluation carried out by two media validators resulted in an average score of 83.44% with the criteria